Cultivating corporate character how to manage the border between the past and the future - Wilkins, Alan L.; Jossey-Bass Publishers (San Francisco, CA. : Jossey-Bass Publishers, 1990)
The programs contains the guides in building the corporate image includes managing the past and the future, guarding border between old and new cultures and the way to sustains the corporate character
What happened on the way to corporate excellence. -- Honoring the past while building for the future. -- Guarding the border between old and new cultures. -- Sustaining a distinctive corporate character
Keywords: Organizational change; Organizational effectiveness